Segurança jurídica extrajudicial e precedentes administrativos: uma investigação sobre a aplicação de precedentes do Cade a partir da análise dos mapas de citação. - Barros, Marco Antonio Loschiavo Leme de (2014)
This dissertation is based on the observation that several administrative centers, today, due to legal reasons, are adjudicatory centers, like actual administrative courts. In order to understand the operation of these decision-making centers, beyond the discussion about its legal fundaments, the study was focused on the actual performance of these administrative courts. To this end, the study focused on the application of administrative precedent as justification of the decisions of the Brazilian Administrative Council for Economic Defense (Cade). The study contributes for this debate due to the following reasons: (i) having identified the existence and application of administrative precedent in Brazilian legal system, it is an objective to see that, within the administrative function, extrajudicial legal certainty is produced from the systematization of administrative decisions, and (ii) there is an interest in rationalizing these decisions in order to make clear the positions of these tribunals to citizens, making it impossible that in the same circumstances courts produce conflicting decisions. The point to stress is that legal certainty doesn’t rely only in judicial decision. On the contrary, the vast majority of activity produced by law, including interpretative, happens beyond the judicial activity. The study of the performance of the Administrative Tribunal of Cade is relevant in this way, due to the prominent role that it plays today in the Brazilian antitrust defense system. This research has an empirical aspect, since it seeks to understand how the administrative precedents operate in the Brazilian legal system - which lacks organized systematization and tradition of applying precedents. The main purpose of this research was to develop a methodology (decision map) to study the application of precedent, particularly to identify precedents; afterwards, it was investigated how the production of extrajudicial legal certainty can or cannot occur with the systematization and the respect for administrative precedent.